2012
DOI: 10.1007/s12149-012-0623-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between symptoms and bone scintigraphic findings in patients with complex regional pain syndrome?

Abstract: The probability of positive bone scintigraphy increased significantly in patients with vasomotor symptoms and in patients with motor and/or trophic changes. This may contribute to the reported variability of the diagnostic performance of bone scintigraphy in CRPS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Moreover, 3 prospective studies have been also published [26,27,30] confirming the usefulness of TBPS as additional tool in doubtful cases [30] and when the duration of the pathology is shorter than 3 [26] or 5 months [27]. Two other retrospective studies [36,37] using the Budapest criteria were also recently published. Moon et al [36], found a low utility of TBPS for diagnosis of CRPS and AlSharif et al [37] found a positive scintigraphy in patients with vasomotor symptoms, motor and/or trophic changes, with a duration of less than 3 months.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, 3 prospective studies have been also published [26,27,30] confirming the usefulness of TBPS as additional tool in doubtful cases [30] and when the duration of the pathology is shorter than 3 [26] or 5 months [27]. Two other retrospective studies [36,37] using the Budapest criteria were also recently published. Moon et al [36], found a low utility of TBPS for diagnosis of CRPS and AlSharif et al [37] found a positive scintigraphy in patients with vasomotor symptoms, motor and/or trophic changes, with a duration of less than 3 months.…”
Section: Discussionmentioning
confidence: 94%
“…Two other retrospective studies [36,37] using the Budapest criteria were also recently published. Moon et al [36], found a low utility of TBPS for diagnosis of CRPS and AlSharif et al [37] found a positive scintigraphy in patients with vasomotor symptoms, motor and/or trophic changes, with a duration of less than 3 months. In our study, TBPS was also particularly helpful when it was performed in the first 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…[40, 41, 46, 48, 49] Seven studies [3032, 3638] did not report on the diagnostic criteria used for the diagnosis of CRPS 1 and two studies [33, 39] used other clinical criteria In total 13 studies were included in the analysis of the influence of patient characteristics on the proportion of positive bone scans. [29, 34, 42, 43, 45, 47, 5056] We included five studies using the IASP criteria [34, 5255] and one study using the Budapest criteria [51] that reported results on the sensitivity of BS in patients meeting the clinical diagnostic criteria for the diagnosis of CRPS 1. The extracted information for each study used for the diagnostic meta-analysis is provided in S4 Table.…”
Section: Resultsmentioning
confidence: 99%
“…Potentially useful tests include thermography (to document skin temperature asymmetry) and volumetry (to document the extent of edema). Triple-phase bone scan results may correspond with the clinical CRPS diagnosis to some degree, 7,250 but this test is neither definitive nor necessary for diagnosis. CRPS may occur with pain that is not responsive to pharmacologic sympathetic blockade, so diagnostic sympathetic blocks are unnecessary.…”
Section: Dimension 2: Common Features Including Epidemiology and Lifmentioning
confidence: 99%